Protective Effect of Minocycline Hydrochloride on the Mouse Embryonic Development Against Suboptimal Environment - Hou, Xiaojing; Cai, Changming; He, Yuanlin; An, Shiyu; Zhao, Shuqin; Sun, Hao; Yang, Yang (Frontiers in Cell and Developmental Biology, 2022)
Numerous studies have reported how inner cell mass (ICM) and trophectoderm (TE) was determined during the process of early mouse embryonic development from zygotes into organized blastocysts, however, multiple mysteries still remain. It is noteworthy that pluripotent stem cells (PSCs), which are derived from embryos at different developmental stages, have identical developmental potential and molecular characteristics to their counterpart embryos. Advances of PSCs research may provide us a distinctive perspective of deciphering embryonic development mechanism. Minocycline hydrochloride (MiH), a critical component for maintaining medium of novel type of extended pluripotent stem cells, which possesses developmental potential similar to both ICM and TE, can be substituted with genetic disruption of Parp1 in our previous study. Though Parp1-deficient mouse ESCs are more susceptible to differentiate into trophoblast derivatives, what role of MiH plays in mouse preimplantation embryonic development is still a subject of concern. Here, by incubating mouse zygotes in a medium containing MiH till 100 h after fertilization, we found that MiH could slow down embryonic developmental kinetics without impairing blastocyst formation potential. Olaparib and Talazoparib, two FDA approved PARP1 inhibitors, exhibited similar effects on mouse embryos, indicating the aforementioned effects of MiH were through inhibiting of PARP1. Besides, we showed an embryonic protective role of MiH against suboptimal environment including long term exposure to external environment and H2O2 treatment, which could mimic inevitable manipulation during embryo culture procedures in clinical IVF laboratory. To our knowledge, it is not only for the first time to study MiH in the field of embryo development, but also for the first time to propose MiH as a protective supplement for embryo culture, giving the way to more studies on exploring the multiple molecular mechanisms on embryonic development that might be useful in assisted reproductive technology.